2007
DOI: 10.1097/mol.0b013e3282a66099
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve stenosis: an active atheroinflammatory process

Abstract: Recent findings regarding the interaction of inflammatory cells, lipids, mediators of calcification, and renin-angiotensin system in stenotic valves support the current opinion of aortic valve stenosis being an actively regulated disease, potentially amenable to targeted molecular therapy. Evidence from prospective clinical studies is eagerly awaited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 79 publications
1
82
0
6
Order By: Relevance
“…11,16,17 Yet, the exact role of inflammation in the pathophysiology of aortic stenosis remains unknown. The aim of this study was to associate the local inflammatory response, exerted in aortic valves through the leukotriene (LT) pathway, with the clinical features of valvular function as determined echocardiographically.…”
Section: Clinical Perspective On P 1325mentioning
confidence: 99%
“…11,16,17 Yet, the exact role of inflammation in the pathophysiology of aortic stenosis remains unknown. The aim of this study was to associate the local inflammatory response, exerted in aortic valves through the leukotriene (LT) pathway, with the clinical features of valvular function as determined echocardiographically.…”
Section: Clinical Perspective On P 1325mentioning
confidence: 99%
“…With regard to pathophysiology, it has been proven that early lesions of AVC implicate active processes similar to atherosclerosis, such as lipid deposition, macrophage infiltration, and production of osteopontin as well as other proteins (Rajamannan, 2010). Further changes associated with extracellular matrix remodeling and neovascularization ultimately lead to active calcification (Prasad and Bhalodkar, 2004;Helske et al, 2007). Experimental animal models of AVC (Rajamannan et al, 2005;Drolet et al, 2006) demonstrated that early lesions contained inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have provided evidences that inflammation plays a key role in the physiopathology of AS as well as classical cardiovascular risk factors such as hypertension, hypercholesterolemia, diabetes, smoking, age or sex [2]. Degeneration of the valve begins with an endothelial dysfunction in the aortic side as a result of the abovementioned risk factors.…”
Section: Aortic Stenosismentioning
confidence: 99%
“…Additionally, metabolomic fingerprinting involves less up-front method development when compared with targeted approaches but requires an exhaustive analysis due to the large number of identified metabolites. As well as in proteomics analyses, there are three main steps when performing a metabolomic study: [1] sample preparation; [2] metabolite detection and [3] data analysis.…”
Section: Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation